The Integration of ASEAN-5 Capital Market after the Donald Trump Election - Tarsisius Renald Suganda; Anneth Regina Hariyono (Jurnal Keuangan dan Perbankan, 2018)
Donald Trump’s victory as the 45th President of the United States had negative responses on the ASEAN countries, especially on the stock market performance. This study conducted to investigate the existence of integration and contagion effect on the capital market of the ASEAN-5 countries after the election of Donald Trump. The five countries used in the research were Indonesia, Singapore, Malaysia, Thailand, and the Philippines. The five countries selected based on the highest FDI (foreign direct investment) flows among other ASEAN countries. Vector Error Correction models (VECM) and Granger Causality tests used as the analysis tools in the study. The daily closing stock price index of ASEAN-5 countries in 2016–2017 collected to be analyzed. The result of VECM model analysis and Granger causality test found the integration and contagion effect of the capital market in ASEAN-5 countries. The Granger Causality test showed that the Philippines had a contagion effect from other ASEAN-5 countries after the election of Donald Trump as the 45th President of the United States. In addition, it also found a two-way causal relationship between Singapore and Thailand, which showed that these two countries gave each other contagion effects.JEL Classification: G31, G32, G34DOI: https://doi.org/10.26905/jkdp.v22i4.1990